2016
DOI: 10.1097/md.0000000000005201
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects intensive medical therapy on the development and progression of subclinical atherosclerosis and the metabolic syndrome in Chinese patients with type 2 diabetes mellitus

Abstract: Background:Few studies have investigated the progression of subclinical atherosclerosis and metabolic syndrome (MetS) in Chinese patients with type 2 diabetes mellitus (T2DM). This study was to compare the long-term effects of intensive medical therapy on the development and progression of subclinical atherosclerosis and MetS in Chinese T2DM patients with that of a conventional treatment regimen.Methods:A total of 316 T2DM patients were randomized to receive conventional pharmacological treatment or intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Human gene INS (insulin) contains a known SNP marker (rs5505) of neonatal diabetes mellitus mediated by hyperinsulinemia [15], which in turn is a well-known physiological marker of atherosclerosis [103,104]. Around rs5505, we selected three more unannotated SNPs able to cause the same hyperinsulinemia (e.g., rs1389349459) and thereby atherogenesis (Table 4).…”
Section: Human Genes Associated With Autoimmunity-associated Diseasesmentioning
confidence: 99%
“…Human gene INS (insulin) contains a known SNP marker (rs5505) of neonatal diabetes mellitus mediated by hyperinsulinemia [15], which in turn is a well-known physiological marker of atherosclerosis [103,104]. Around rs5505, we selected three more unannotated SNPs able to cause the same hyperinsulinemia (e.g., rs1389349459) and thereby atherogenesis (Table 4).…”
Section: Human Genes Associated With Autoimmunity-associated Diseasesmentioning
confidence: 99%
“…Generally, blood sugar levels between 70 mg/dL (3.9 mmol/l) and 100 mg/dL l (5.6 mmol/) are considered normal. It is evident that glucose variability (GV) plays a role in the development of diabetic complications, particularly cardiovascular events [ 4 , 5 ]. FPG variability is an important predictor of mortality, especially in patients with poor glycemic control [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…VSMCs play a crucial role in the development and progression of AS 24,25 since VSMCs regain their proliferative properties when they are activated by certain pathological conditions, such as a variety of proinflammatory stimuli 26,27 . Several studies have shown that the proliferation and migration of VSMCs are significantly promoted in AS and contribute to AS progression 3,4,28 . Therefore, inhibiting the proliferation and migration of VSMCs might be a potential strategy for curing AS.…”
Section: Discussionmentioning
confidence: 99%
“…Both vascular endothelial cells and vascular smooth muscle cells (VSMCs) play major roles in the development of AS. Previous studies showed that the proliferation and migration of VSMCs was significantly promoted in AS, which might accelerate pathological processes 3,4 . However, comprehensive molecular investigations have not been fully reported regarding preventing VSMCs from highly proliferating and migrating.…”
Section: Introductionmentioning
confidence: 99%